2006
DOI: 10.15809/irriga.2006v11n3p319-327
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação De Um Sistema Irrigação Por Aspersão Com Aplicação Do Inversor De Freqüência No Conjunto Motobomba

Abstract: AVALIAÇÃO DE UM SISTEMA IRRIGAÇÃO POR ASPERSÃO COM APLICAÇÃO DO INVERSOR DE FREQÜÊNCIA NO CONJUNTO MOTOBOMBA  João Alberto Borges de Araújo1; Odivaldo José Seraphim2; Jair Antonio Cruz Siqueira3; Fernando Presenço4; Fernando de Lima Caneppele41 Departamento de Engenharia de Produção, Faculdade de Tecnologia, Botucatu, SP,  araujo@fca.unesp.br2Departamento de Engenharia Rural, Faculdade de Ciëncias Agronömicas, Universidade Estadual Paulista, Botucatu, SP 3CCET – Universidade Estadual do Oeste do Paraná, Cascav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Córcoles et al (2019) evaluated the feasibility of using variable-frequency drives to capture water from wells for irrigation and found energy savings ranging from 6.8 to 23%, depending on the characteristics of the irrigated areas and the dynamic variations of the water depth in the well. Araújo et al (2006) obtained a power reduction of around 30% when using a variable-frequency drive in a conventional sprinkler system, considering the number of lateral lines in simultaneous operation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Córcoles et al (2019) evaluated the feasibility of using variable-frequency drives to capture water from wells for irrigation and found energy savings ranging from 6.8 to 23%, depending on the characteristics of the irrigated areas and the dynamic variations of the water depth in the well. Araújo et al (2006) obtained a power reduction of around 30% when using a variable-frequency drive in a conventional sprinkler system, considering the number of lateral lines in simultaneous operation.…”
Section: Resultsmentioning
confidence: 99%
“…It occurs because the initial investment for the acquisition of valves is higher than for the acquisition of the variable-frequency drive, the latter still providing a reduction in the cost related to energy consumption. The annual irrigation time was decisive for the feasibility of the use of the variable-frequency drives in other irrigation systems (Carvalho et al, 2000;Araújo et al, 2006;Córcoles et al, 2019). Araújo et al (2006) found the leveling point between the number of hours worked and the economic feasibility of variable-frequency drives in center pivot motor-pump sets, considering various powers of drives associated with different working pressures.…”
Section: Cmentioning
confidence: 99%
See 3 more Smart Citations